SELF-IDENTITY AND SOCIAL IDENTITY AS DRIVERS OF CONSUMERS’ PURCHASE INTENTION TOWARDS LUXURY FASHION GOODS AND WILLINGNESS TO PAY PREMIUM PRICE - Suha Fouad Salem; Sharif Omar Salem (Asian Academy of Management Journal, 2018)
The main purpose of this study is to examine consumer behaviour towards purchasing luxury fashion goods based on an extended model that integrates the constructs of theory of planned behaviour (TPB), social identity, self-identity, and price premium. The proposed model is examined using a self-structured questionnaire with a dataset of 395 valid responses. Statistical analysis is based on the PLS-SEM approach with the use of Smart-PLS software 3.2.0. The results indicate that all the hypotheses associated with the relationships between social identity and TBP determinants and between self-identity and TBP determinants are supported; however, the hypothesis on the relationship between selfidentity and subjective norm is not supported. Moreover, the hypotheses associated with the relationships between TPB determinants, subjective norm, perceived behavioural control (PBC), attitude, and intention to purchase luxury fashion are also supported. Finally, the proposed relationships between intention to purchase luxury fashion and model outcome, purchase of luxury fashion and intention for price premium are supported as well. This study is the first that integrates social identity, self-identity, and price premium with TPB to explain consumers’ purchase behaviour towards luxury fashion products. The findings can help marketers develop effective marketing strategies in order to stay competitive.